ENHANCING STORAGE AND RETRIEVAL SYSTEM IN THE CONSIGNED GOODS WAREHOUSE: A KAIZEN-BASED SOP DEVELOPMENT AND IMPLEMENTATION - Aji, Sonny; Nindiani, Aina (Industry Xplore, 2025)
The consigned goods warehouse often faces challenges, including accumulating of stored items and faults in retrieving consigned goods. These problems stem from using simple forms with inadequate information and the absence of a Standard Operating Procedure (SOP) to regulate consigned goods in the warehouse. This research aims to develop and implement an SOP for storing and retrieving consigned goods to address these issues. The research process began with observations and needs analysis, followed by the development and implementation of the SOP, and concluded with an impact analysis comparing conditions before and after the implementation of Kaizen. The findings reveal that the consigned goods warehouse system has become more organized and standardized. Improvements in item information include adding details such as intended usage, usage timelines, item photographs, and Purchase Requisition (PR) documents or Statement Letters (BA). These enhancements have improved traceability and eliminated faults in retrieving consigned goods. The accumulation of items was mitigated through a storage time limit and reminders from warehouse personnel to users when it was time to use the items.